Kearifan Lokal Sasak Dan Pengembangannya Dalam Pendidikan Literasi Financial Di Lingkungan Keluarga - Baiq Yuliana Rizkiwati; Huzain Jailani; Muhammad Zainul Majdi (Universitas Hamzanwadi, 2023)
Maximizing the process of economic educationonly through formal educationwould not be sufficient, instead, it needs to be supported by informal economic education. This study is aimed to 1) analyze the forms of Sasak’s local wisdom in family economic education, 2) develop theguidebookfor family economic education that is based on Sasak’s local wisdom as a guide for parents. Samples in this study were amounted to 35 Sasak parents. This study used a mixed-methods approach,observation and in-depth interview were used as the techniqueto analyzethe data of the forms of Sasak’s local wisdom. The Design-Based Research (DBR) development model was used to develop the guidebook for family economic education based on Sasak’s local wisdom. Observation and in-depth interview results of the study found that the forms of Sasak’s local wisdom in the financial management field of family economic education, encompass:1) Itiq, 2) Penunah, 3) Semaiq-maiq, 4),Saling peliwat.The research data of the guidebook developmentof family economic education based on Sasak’s local wisdom were determined as valid, indicated by the percentage of material experts’ judgement that amounted to 80.9%, and 85.33% of design experts’ judgement, which is very valid. The product fulfilled the practicality criteria based on the results of the parent response questionnaire, with a percentage of 83.4%, which means that the product is proper to use